ISLAMIC EDUCATION MANAGEMENT STRATEGIES IN IMPROVING THE QUALITY OF ISLAMIC RELIGIOUS EDUCATION INSTITUTIONS - Fatiha, Nurul; Ulhaq, Syahirah; Ramdani; Habib, Syafaatul (International Journal of Multidisciplinary Reseach, 2025)
This study explores strategies in Islamic education management aimed at improving the quality of Islamic educational institutions. Educational quality is a vital indicator of an institution’s success in fulfilling its vision and mission. In the context of Islamic education, effective management requires the integration of Islamic values with professional administrative practices. This research uses a library research method, gathering information from books, journals, and relevant literature. The sources are divided into primary—such as books, scientific articles, and journals directly discussing Islamic education management—and secondary sources that remain relevant to the topic. The study finds that strategic planning, Islamic leadership, human resource development, and continuous evaluation are essential elements in enhancing educational quality. Moreover, the active involvement of stakeholders, including teachers, students, and parents, contributes significantly to creating a positive and effective learning environment. These strategies support the sustainability and excellence of Islamic educational institutions in facing future challenges.